The significance of assessment the relationship between the level of 25-(OH) vitamin D and excessive body weight in women on preconceptional period and during pregnancy - Maksymenko, L.R.; Perkhulyn, O.M.; Drohomyretska, N.V.; Henyk, N.I. (Medicni Perspektivi, 2023)
The goal of this study was to determine the association between the level of 25-(OH) vitamin D and excessive body weight in women on preconceptional period and during gestation. There were studied 117 women. The first group included 68 overweight women (body mass index (BMI) 25.0-29.9 kg/m2), the second – 49 with normal body weight (BMI 18.5-24.9 kg/m2) before prepregnancy. Anthropometry was performed, BMI (kg/m2) by Quetelet formula. The 25-(OH) vitamin D blood serum level was studied by immunoenzymatic method. Fasting blood serum levels of glucose, insulin were determined by the immunoenzymatic method, insulin resistance index was calculated, serum concentrations of triglycerides, total cholesterol, high, low and very low density lipoproteins were determined. The results were statistically analyzed using Statistica 10 (Serial Number: STA999K347150-W) and MEDCALC®. It was found an inverse correlation between the level of vitamin D and BMI (r= – 0.71, p<0.001). Excessive body weight on preconceptional period reduces the chances of an adequate level of vitamin D (0.02; 0.00-0.10; p<0.001) and increases the chances of its deficiency (13.11; 4.89-35.30; p<0.001) during early gestational period. It was diagnosed that during pregnancy, the chances of vitamin D deficiency increase in women with normal body weight (3.16; 1.11-9.02; p=0.04), but remain significantly higher in the overweight (6.30; 2.80-14.18; p<0.001). It was shown that insufficiency/deficiency of vitamin D during pregnancy was accompanied by insulin resistance, hyper/dyslipidemia, which are the metabolic basis of gestational complications. The assessment of an inverse relationship between the level of 25-(OH) vitamin D and excessive body weight in women on preconceptional period and the increase of deficiency during pregnancy should be taken into account for the purpose of laboratory determination of the vitamin at the stage of pregnancy planning for the appointment of therapeutic correction.